Wychowawca wsparciem dla ucznia? Relacje uczeń – wychowawca w percepcji gimnazjalistów - Piorunek, Magdalena; Werner, Iwona (Wydawnictwo Naukowe UAM, 2014)
It is generally accepted that the school plays a number of functions. The function of school aid involves supporting, advising, assistance, mentoring, training, coaching and therapy and the class teacher should play a special role in the educational system of assistance. The main objective of the study was to investigate how students perceive the class teacher, especially in the context of establishing relationships and coping with students’ behavioral difficulties and personal problems. The paper presents selected results of a research conducted in lower secondary schools with a diagnostic survey method (N = 393 students). The results indicate that teachers are of little support for students and the roles they perform are primarily educational and formal.
Is the Class Teacher the Student’s Support? Student-Teacher Relations in the Perception of the Lower Secondary School Students
Keywords: class teacher; lower secondary school student; student-teacher relations; support